Team-level success factors in agile organizations - Jonsson, August; Ran Ragnadottir, Maria (My University, 2022)
The business environment of today is rapidly moving and is characterized by complexity and uncertainty. These conditions have made numerous companies replace their traditional way of organizing with less hierarchical forms, in attempts of adapting to the new business landscape. In the software development sector, agile methodologies have gained a strong foothold, seeing companies transition their architecture to a more flexible structure built around self-managing teams. Although there is a wide array of studies treating agile methodologies and self-managing teams, there is a scantiness of literature addressing empirical research on self-managing teams in an agile context and what they consider as the factors making their teams successful. Furthermore, multiple papers treat factors that mediate a team’s success, however, few of them consider these factors’ order of importance or how they can be measured. This research departs from previous studies on self-managing teams in agile organizations and aims to bridge the mentioned knowledge gap. In this study, Zenseact, a software development company in the automotive sector, is investigated in a single-case research project. Since its birth, Zenseact has embraced the new business environment by employing agile methodologies and the traditional company departments have been discarded in favor of self-managing teams in a dynamic organizational structure. With this background, Zenseact has been deemed an appropriate organization for investigation, and to explore what makes their self-managing teams successful. Followingly, the researchers distilled the company’s ambition down to three research questions: - What are the team-level success factors in self-managing agile teams? - What method(s) can be used to measure the employees’ perception of these success factors? - Which team-level success factors do employees regard as most important for their team´s success? The researchers approached the study by first constructing a conceptual framework, which served as guidance for the data collection and the analysis. Secondly, data on the employees’ perception of success and what makes their teams successful was collected through interviews, observations, a survey, and company documents. Thirdly, the collected data was contrasted against literature. Finally, how the findings contribute to research and practice was elaborated upon. In general, the factors making teams successful at Zenseact were aligned with the factors presented in literature, although with some deviations. The data collection resulted in 15 different success factors. Among these 15, the five that were considered the most important were: Trust, Communication, Respect, understanding, and acceptance, Task satisfaction, and Team morale. Furthermore, the study suggested that the success factors, through their intangible nature, are difficult to quantify, but could be measured through reoccurring self evaluation surveys, where the direction of change in satisfaction is studied. The primary insights from this study are that the strict interpersonal success factors (e.g., trust, communication, and respect, understanding, and acceptance) are considered predominantly crucial for the success of self-managing agile teams. This brings further understanding to the field, as these factors have previously been portrayed as important for a team’s success but without regards to their order of significance.
Keywords: Team level success; Self-managing teams; Agile teams; Teamwork; Team-level success factors